Autovaloracióny su relación con el rendimiento, la autoeficacia y otras variables psicológicas en yudocas nacionales - Monte del Monte, L. M.; Zaldivar Pérez, D. (Revista Cubana de medicina del deporte y la cultura fisica, 2018)
In this research, self-evaluation of the performance qualities recorded a week before the competence is related with the self-efficiency of the female judo players before competing with the evaluation of the opponents during the competition with the changes of the "Yes, I can" inner dialogue before adversities in the competition with the sports performance and with thecauses attributed to the mistakes made in competition. A relationship between these variables is established highlighting the influence of the self-evaluation adequacy over self-efficiency, over the stability of the "Yes, I can" dialogue before adversities, over the adequacy of the opponents evaluation and over the causes attributed to mistakes made in the competition. The underestimation of the performance qualities is the inadequacy of the most affected self-evaluation and the adequacy of the self-evaluation is the most effective one for the sports performance.